Perbedaan Perilaku Seksual Pranikah Remaja Menurut Kedekatan Tempat Tinggal dengan Lokalisasi - Isnadia, Hikmah Ayu; Azinar, Muhammad (Indonesian Journal of Public Health and Nutrition, 2021)
Background: adolescence is a period of growth and development, which has a high sense of curiosity and period of searching for identity that is easily influenced by the environment. Adolescents who live in localization are accustomed to exposure promiscuous sexual behaviour. HIV/AIDS’s cases tend to increase every year in Grobogan Regency, the number of cumulative cases upto 2019is 615 HIV casec and 647 AIDS cases. The purpose of this study was to determine the differences in premarital sexual behavior of adolescents who live near brothels and far from brothels. Methods: this research was a quantitative study with a cross sectional approach. Sample were 215 for villages near to brothels and 172 for villages far from brothels using the purposive sampling technique. The instrument used was a questionnaire. Data were analyzed using the Chi Square test with the alternative Fisher's test and Unpaired T Test with the alternative Mann Whitney test. Results: the results showed that were differences in premarital sexual behaviour (p value = 0,000), knowledge about reproductive health (p value = 0.004) and contact with localization (p value = 0.000) between adolescents who were near to brothels and far from brothels. Conclusion: there are differences in premarital sexual behaviour, knowledge, and contact with brothels between adolescents who are live near to brothels and far from brothels. There are no differences in attitude, parental influence, peer roles, sources of information, level of religiosity, norms, and self efficacy between adolescents who are live near to brothels and far from brothels. Keywords: Adolescence, Far From Brothels, Near From Brothels, Premarital Sexual Behaviour